Interlanguage: near or far frontier? Approaching the importance of pragmatics (Ogigia. Revista Electrónica de Estudios Hispánicos, 2020)
This article aims to contribute to studies that promote the development of pragmatic competence in E/LE classroom. We will start the analysis of some oral statements of a corpus in which interviews-conversations of Italian learners are collected. Emphasis will be placed on the effects of this lack of competition in the interaction and their impact on learning.
Keywords: Pragmatic competence; SFL; interaction; interlanguage